The utility of the Edinburgh Depression Scale as a screening tool for depression in Parkinson's disease. (15th April 2014) - Baillon, Sarah; Lindesay, James; Prabhakaran, Pravin; Hands, Oli; Murray, Jonathan; Stacey, Suzanne; Gaur, Sandhya; Rajkonwar, Aniruddha; Padmanabhan, Jayaraj; Shukla, Deepak; Chakrabarti, Santanu; Lo, Nelson; et al.
<x xml:space="preserve">Abstract</x> Objective This study aimed to evaluate the Edinburgh Depression Scale (EDS) as a screening tool for use in a Parkinson's disease (PD) population. Many commonly used depression scales include items relating to somatic symptoms that also occur in PD, which could potentially result in inaccurate reporting of depressive symptoms. The EDS is a scale that incorporates no somatic items. Method One hundred twenty patients attending specialist PD clinics were assessed using a standardised diagnostic interview (Present State Examination—Schedules for Clinical Assessment in Neuropsychiatry) to establish a diagnosis of DSM‐IV depression. They later completed the EDS with another researcher who was blind to the results of diagnostic interview. A receiver operating characteristic curve analysis was carried out to identify the optimal threshold score on the EDS and the Brief EDS to identify any depressive disorder or major depression. The performance characteristics at a range of thresholds were compared. Results A cut‐off score of 10/11 gave maximal discriminant validity, with 74% sensitivity, 92% specificity and 64% positive predictive value for the identification of any depression according to DSM‐IV criteria. Conclusions This study suggests that the EDS is both a valid and potentially useful instrument that can be used as a quick self‐completion questionnaire for screening for depression in people who have PD. Copyright © 2014 John Wiley & Sons, Ltd.